Factors Influencing Delays in Patient Access to New Medicines in Canada: A Retrospective Study of Reimbursement Processes in Public Drug Plans - Salek, Sam; Lussier Hoskyn, Sarah; Johns, Jeffrey Roy; Allen, Nicola; Sehgal, Chander (Frontiers in Pharmacology, 2019)
Individuals who rely on public health payers to access new medicines can access fewer innovative medicines and must wait longer in Canada compared to major markets around the world. New medicines/indications approved by Health Canada and reviewed for eligibility for reimbursement by the Common Drug Review or the pan-Canadian Oncology Drug Review (CDR/pCODR) from the beginning of 2012 through to the end of December 2016 were analysed, with data taken from the relevant bodies’ websites and collected by IQVIA. This analysis investigated individual review segments - Notice of Compliance (NOC) to Health Technology Assessment (HTA) submission, HTA review time, pan-Canadian Pharmaceutical Alliance (pCPA) negotiation time, and public reimbursement decision time, and analyzed the trends of each over time and contributions to overall time to listing decisions. Average overall timelines for public reimbursement after NOC were long and most of this time is taken up by HTA and pCPA processes, at 236 and 273 days, respectively. This study confirms that Canadian public reimbursement delays from 2013-2014 to 2015-2016 lengthened from NOC to listing (Quebec +22%, first provincial listing +38%, and country-wide listing +53%), reaching 499, 505, and 571 days, respectively. Over the same period, time from NOC to completion of HTA has increased by 33%, and time from post-HTA to first provincial listing by 44%. The pCPA process appears to be the main contributor to this increasing time trend, and although some provinces could be listing more quickly post-pCPA, they appear to be listing fewer products. Reasons for large delays in time to listing include the many-layered sequential process of reviews conducted before public drug plans decide whether to provide access to new innovative medicines. Although there has been some headway made in certain parts of the review processes (e.g. pre-NOC HTA), total time to listing continues to increase, seemingly due to the pCPA process and other additional review processes by drug plans. More clarity in the pCPA and provincial decision-making processes and better coordination between HTA, pCPA, and provincial decision-making processes is needed to increase predictability in the processes and reduce timelines for Canadian patients and manufacturers.